Anatomy and Physiology of Animal Model Rats in Biomedical Research - Hidayat, Rachmat; Patricia Wulandari (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
A distinguishing feature of rodents, including rats, is the absence of canines and thepresence of prominent incisors. Rats are monophydontic, meaning they grow one setof teeth in their lifetime. The enamel of the rodent incisor contains iron, which givesit its yellow-orange color. Rats are mammals and as such, possess many similaritieswith other mammals. Only the peculiarities of the rat’s anatomy are addressed. Malerats reach puberty at 40 - 60 days of age. Descent of the testes usually occursbetween days 30 - 60. Sperm counts vary by strain. The male rat has an os penis.Male rats have the following accessory sexual organs: ampulla, seminal vesicles,prostate, bulbourethral glands, coagulating glands, and preputial glands. Thecoagulating gland and prostatic and vesicular secretions are responsible for thecopulation plug, a firm plug deposited in the vagina of the female after copulation.(This plug, when found outside the female rat, is capsuleshaped and approximately5 mm long.) The male rat has no nipples. The adult male rat has a prominentscrotum and a longer anogenital distance than the female rat.